Socio-Economic Position of Peasants in the Russian Far East in 1922–1941 - Pikalov, Yuri V. (Opción, 2019)
The research objective is to study the socio-economic position of peasants in the Far East of Russia during transition from the market economy to the Soviet administrative command economy via comparative qualitative research methods. As a result, collectivization was determined by political goals rather than economic reasonability. In conclusion, Russia’s federal and local authorities receive good reasons to pursue more active and efficient policy of giving the land to Russia’s citizens, who wish to develop the agriculture in the Far East.